Determination of Very Low Level of Free Formaldehyde in Liquid Detergents and Cosmetic Products Using Photoluminescence Method - Ali Gholami; Atefeh Mohsenikia; Saeed Masoum (Journal of Analytical Methods in Chemistry)
Formaldehyde is commonly used in detergents and cosmetic products as antibacterial agent and preservative. This substance is unfavorable for human health because it is known to be toxic for humans and causes irritation of eyes and skins. The toxicology studies of this compound indicate risk of detergents and cosmetic formulations with a minimum content of 0.05% free formaldehyde. Therefore, determination of formaldehyde as quality control parameter is very important. In this study, a photoluminescence method was achieved by using 2-methyl acetoacetanilide. Also, the Box-Behnken design was applied for optimization of Hantzsch reaction for formaldehyde derivatization. The investigated factors (variables) were temperature, % v/v ethanol, reaction time, ammonium acetate, and 2-methyl acetoacetanilide concentration. The linear range was obtained from 0.33–20 × 10−7 M (1–60 μg·kg−1) and the limit of detection (LOD) was 0.12 μg·kg−1. The proposed method was applied for the analysis of Iranian brands of liquid detergents and cosmetic products. The formaldehyde content of these products was found to be in the range of 0.03–3.88%. Some brands of these products had higher concentration than the maximum allowed concentration of 0.2%. High recoveries (96.15%–104.82%) for the spiked dishwashing liquid and hair shampoo indicate the proposed method is proper for the assessment of formaldehyde in detergents and cosmetic products. The proposed methodology has some advantages compared with the previous methods such as being rapid, without the necessity of applying separation, low cost, and the fact that the derivatization reaction is carried out at room temperature without any heating system.